Insights into the phenolic composition and bioactive properties of Aloe vera flower - Añibarro-Ortega, Mikel (2021)
Aloe vera leaf has been subject of several scientific studies that aimed to characterize compositional and biological properties.1,2 However, the flower (Figure 1) remains an underexploited plant part. Aiming the prospection of bioactive phytochemicals in this plant matrix, this study was focused on the analysis of phenolic compounds and in vitro antioxidant, antimicrobial, and tyrosinase inhibition activities. A dried powder of Aloe vera flower underwent a solid-liquid extraction with an hydroethanolic mixture for 1 h, and the phenolic profile of the obtained dried extract was characterized by HPLC-DAD- ESI/MSn. Regarding biological activities, the antioxidant activity was evaluated by the cellular assays of OxHLIA and TBARS, using sheep erythrocytes and porcine brain cells as oxidizable substrates, respectively, and by the β-carotene bleaching inhibition assay; the antimicrobial activity was screened against skin-associated pathogenic bacteria and fungi; and the capacity to inhibit the activity of the tyrosinase enzyme was tested using L-DOPA as a substrate. It was found a phenolic profile constituted mainly by the flavonoids apigenin-6,8-C-diglucoside, apigenin-2’’-O-pentoxide-C-hexoside, apigenin-6-C-glucoside, and traces of luteolin glucoside derivatives (accounting for 93.4% of the extract), and by the phenolic acid 5-O-caffeoylquinic acid. As far as we know, it is the first time that some of these compounds are described in Aloe vera flower. No anthraquinone glycosides were detected in this part of the plant. The extract revealed an interesting antioxidant activity, being able to protect the erythrocyte membranes and the β-carotene from the free radical generated in the in vitro reaction system. It was also able to inhibit and kill multidrug-resistant bacteria such as Pseudomonas aeruginosa and Escherichia coli and some fungi, including Candida albicans. It also inhibited the tyrosinase enzyme activity, which translates its potential as a skin whitening agent. Based on these results, it was concluded that the Aloe vera flower could be exploited by industrial sectors interested in bio-based ingredients due to its composition in flavonoids and antioxidant, antimicrobial, and tyrosinase inhibition properties.